Analisis Stabilitas Lereng Tambang Nikel Kabupaten Morowali - Ramadhani, S.; Minmahddun, A.; Patuti, I.M.; Widiastuti, M. (Tadulako University, 2024)
Central Sulawesi Province is a province that has quite high mining activities, so an evaluation of the stability of open pit slope excavations needs to be carried out to prevent collapses during the exploration process which could result in loss of life. Analysis using the finite element method is one method that can be used to analyze slope deformation and stability during the excavation process. This research simulates excavation of a mine slope in 4 stages with a height of 5 m and a slope of 500. The analysis was carried out based on the results of the N-SPT test at three locations (GT-15617, GT-19125 and GT-19841) which are the slopes with the most extreme slopes. The analysis results show that at GT-15617 the maximum deformation occurred at stage 4 of the excavation at 0.18 m with a safety factor of 1.43, the maximum deformation at the GT-19125 location occurred at stage 4 at 0.21 m with a safety factor of 1.26 and at location GT-19841 maximum deformation occurred at stage 4 of 0.21 with a safety factor of 1.21. The overall safety factor analysis results do not meet the required minimum safety factor criteria.